Social entrepreneurship and social business : An introduction and discussion with case studies - Tokarski, Kim Oliver; Ernst, Kati; Volkmann, Christine K. (Gabler Verlag, 2012)
This compilation offers students a comprehensive overview of the field of social entrepreneurship. Leading European researchers and lecturers such as Ann-Kristin Achleitner, Markus Beckmann, Heather Cameron, Pascal Dey, Andreas Heinecke, Benjamin Huybrechts, Alex Nicholls, Johanna Mair, Susan Müller and Chris Steyaert have contributed to this textbook. Content - The Field: Background, Characteristics, Definitions, Drivers, Challenges - The People: Personality of Social Entrepreneurs, Human Resource Management, Volunteer Motivation, Collaborations and Partnerships - The Business: Business Models, Marketing, Financing, Performance Measurement, Scaling Strategies - The Market: Social Entrepreneurship in the Market System, Impact, Critical Reflections Target Groups Students and lecturers of Business and Economics, in particular those with a focus on social entrepreneurship in Master of Science, Bachelor and MBA programs Social entrepreneurs and organizations supporting social entrepreneurs Editors Prof. Dr. Christine K. Volkmann is head of the Chair of Entrepreneurship and Economic Development at the Schumpeter School of Business and Economics, University of Wuppertal, Germany, and holds the UNESCO Chair of Entrepreneurship and Intercultural Management. Prof. Dr. Kim Oliver Tokarski is a Professor of Business Management and Entrepreneurship as well as head of the Competence Centre on Corporate Business Development at the Bern University of Applied Sciences, Switzerland. Dr. Kati Ernst is a management consultant based in Berlin, Germany.